Spatial inventory of selected atmospheric emissions from oil industry in Ecuadorian Amazon: Insights from comparisons among satellite and institutional datasets. (December 2019) - Durango-Cordero, J.; Saqalli, M.; Parra, R.; Elger, A.
Highlights: Publicly disclosed data were compared to UN official estimates and satellite observations. Estimates from public data were similar to those from UN, thus considered of acceptable quality. Interannual decline of gas flared according to public data suggests greater gas conservation. Airborne emissions with potential impact on health and climate were estimated. Spatially homogenized emissions represent a progress towards hazard mapping. Abstract: Atmospheric emissions from oil activities impact human health, socioeconomic status and exacerbate global warming. This study was conducted in the North-eastern Ecuadorian Amazon, a rich biodiverse and cultural area. This study aimed to show the benefits of public institutional data to advance hazard mapping knowledge for comprehensible risk evaluation. A spatial inventory was built from publicly disclosed reports spanning ten years (2003–2012). Emissions were estimated for gas flaring, associated black carbon (BC) and greenhouse gases (i.e., CO2 and CH4 ). To assess the quality of publicly available data, the calculated emissions were compared with satellite observations and historical energy statistics from the United Nations (UN). Results indicate total gas flared for this period of 7.6 Gm 3, corresponding to 782 Mm 3 yr −1, and equivalent to a 3.7–4.5 kt yr −1 of BC. These values were in agreement with the UN estimates, suggesting that publicly available data are of acceptable quality. In contrast, the results from energy censuses diverged from satellite observation data, which might be explained by a poor calibration of satellite sensors. Study results enabled emissions mapping at a higher spatial scale than previous studies. Black carbon presented the highest results with 29.4–148.0 kg m −2 yr −1 in the cities of Shushufindi and Joya de Los Sachas. Greenhouse gases were up to twenty-fold higher than previous estimates. Publicly disclosed data estimates were discussed in terms of their potential on evaluations for climate, local health and economic impacts, to raise environmental monitoring and accountability in governmental institutions.